Análisis del género como bien público y su función de bienestar social: Elección colectiva vs. elección pública - Antonio Sánchez-Bayón (Atlantic Review of Economics (ARoEc), 2024)
– This is a review on gender issue foundations and its comparative development, to carry out an economic analysis of costs, incentives, efficiency and welfare. Attention is focused on questioning the contributions of Public Economics, trying to de - ideologize gender and address it from the Social Choice and as a public good of state provision and promotion according to its social welfare function. For this review, the theoretical and methodological frameworks of Public Choice (and other New - Institutional appro aches and other complementary heterodox approaches) are used here, with comparative empirical illustrations, so that it is possible to offer a systematization of the negative effects of public intervention in economy, especially in the case of gender and i ts associated paradox.
Keywords: A12; A13; A14; B5; D63; F5; H11; H4; P16; P26; Y8; Z1; 330; Public Economics; New Political Economy; New-Institutional approaches; gender perspective; gender paradox; women's rights; cis & trans feminism